THE IMPORTANCE OF TEACHING A FOREIGN LANGUAGE IN LANGUAGE UNIVERSITIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In our article, the problems of teaching theoretical subjects such as general linguistics, theoretical grammar, lexicology, translation theory, stylistics, and text interpretation are considered using new areas of linguistics. Under the influence of disciplines such as communication linguistics, pragmalinguistics, cognitive linguistics, and linguoculturology, the position is taken and justified that language theory courses in higher education should be significantly updated and supplemented.